Do MD&A Disclosures Help Users Interpret Disproportionate Inventory Increases? - Sun, Yan (The Accounting Review, 2010)
ABSTRACT: This study investigates whether MD&A disclosures have predictive ability for future firm performance in cases of disproportionate inventory increases. Using a sample of 568 manufacturing firms with disproportionate inventory increases, I find that the favorability of explanations for inventory changes in MD&A is positively associated with a firm’s profitability and sales growth in the subsequent three years. I also find that future profitability and sales growth of firms that do not explain disproportionate inventory increases in MD&A fall between those of firms with favorable explanations and firms with unfavorable explanations. These results suggest that the existence and the favorability of MD&A inventory disclosures help users interpret disproportionate inventory increases and predict future firm performance.